Decolonial and postcolonial studies. Theories about modernity, coloniality, and eurocentrism - Martha Isabel Gómez Vélez; Dora Cecilia Saldarriaga Grisales; María Claudia López Gil; Lina María Zapata Botero (Ratio Juris, 2017)
The article is part of one of the specific objectives of which the research project is framed. That is to investigate decolonial studies and their context, as they are platforms for critical theories such as Latin American abolitionism and feminism. As such, the article contextualizes decolonial studies developed in Latin America in recent decades. However, these studies should not be analyzed separately from other fundamental concepts when it comes to addressing decolonial criticisms, such as the relationship between modernity and coloniality and the way in which the eurocentric vision is reflected, also without forgetting an important antecedent to the decolonial theories: the postcolonial studies. For this, a study was carried out starting from the qualitative paradigm, thought of as an effort to understand social reality as a historical process, from a decolonial perspective, because precisely what is sought is to unravel the association to domination in Latin America during the 21st century. This implies the use of a hermeneutical historical approach, which presupposes the bibliographical analysis of multiple authors who have concentrated on the interpretation of the realities generated by colonialism and coloniality.